THE EFFECT OF DUAL ROLE CONFLICTS, JOB STRESSORS AND WORK ENVIRONMENT ON JOB SATISFACTION OF EMPLOYEES OF THE INVESTMENT OFFICE AND ONE-STOP SERVICE OF THE MENTAWAI ISLANDS REGENCY - Edi Hasymi; Sonya Sarifah Absah; Sorija Sorija; Davit Hidayat (SEAN Institute, 2022)
This study aims to see the effect of (1) Dual role conflicts on job satisfaction of DPMPTSP employees of the Mentawai Islands Regency. (2) Job stressors to job satisfaction of DPMPTSP employees of Mentawai Islands Regency. (3) Work environment towards job satisfaction of DPMPTSP employees of Mentawai Islands Regency. (4) dual role conflicts, stressors and work environments have a joint effect on job satisfaction of DPMPTSP employees of the Mentawai Islands Regency. The population in this study was 32 dpmptsp employees of Mentawai Islands Regency. And the technique of determining the number of samples taken as respondents with this sampling technique using the total sampling technique (overall sample) total sampling is a sampling technique where the number of samples is equal to the population (Sugiyono, 2017). The reason for taking the total sampling is because according to (Sugiyono, 2017) the total population that is less than 100 the entire population is used as a sample of all studies. The results of this study show that (1) Dual role conflicts have a negative influence on job satisfaction of DPMPTSP employees of the Mentawai Islands Regency. (2) Job stressors have a negative influence on job satisfaction of DPMPTSP employees of the Mentawai Islands Regency. (3) The work environment has a positive influence on job satisfaction of DPMPTSP employees of the Mentawai Islands Regency. (4) Conflict of dual roles, stressors and work environment together have a significant effect on job satisfaction of DPMPTSP employees of the Mentawai Islands Regency.